KATEGORI PEROKOK BERDASARKAN INDEKS BRINKMAN DAN INSOMNIA - I Gede Purnawinadi (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2020)
One of the human basic is the need to rest. Resting for humans is useful for restoring energy, repairing cells and resting the organs of the body which all day long activity. One way humans rest their bodies is by sleeping. Nicotine is a stimulant, and nicotine side effects can cause insomnia. The purpose of this study was to identify a significant relationship between the degree of smoking based on the Brinkman Index and insomnia through analytical survey research using cross sectional studies. The subjects of this study were people who smoked in Kaima village, Kauditan sub-district, North Minahasa district with a total sampling technique, which amounted to 80 respondents according to the results of the initial survey of researchers through direct interviews. Statistical test results show a significance value (p = 0.009 < 0.05) with a weak correlation coefficient ( r = 0.288) with a positive direction. There is a significant relationship between the degree of smoking and the incidence of insomnia. The community is expected to be able to change smoking behavior by reducing the number of cigarettes consumed or even stop smoking.